KEANEKARAGAMAN SPESIES TUMBUHAN DI AREALNILAI KONSERVASI TINGGI (NKT) PERKEBUNAN KELAPA SAWIT PROVINSI RIAU - Hafizah Nahlunnisa; Ervizal A.M. Zuhud; Yanto Santosa (Department of Forest Resources Conservation and Ecotourism - IPB University, 2016)
Palm oil plantation is important role of increased economic in Indonesia. Beside of that, the exsistence of palm oil plantation has negative effect in ecology, that is decreasead of plant diversity. The area of high conservation value (HCV) is an effort to reducing the negative impact of oil palm plantation. The purpose of this study is to identify the level of diversity of plant species and forms of community interaction in the area of HCV. It is can used to basic of management of HCV areas that can be exploited in a sustainable manner. Data collected in the three palm oil companies in Riau Province that PTPN V, PT Mitra Unggul Pusaka (MUP), and PT Ivomas Tunggal on March till April 2016. The data collection was using a single plot and interviews. Data were analyzed using Margalef diversity index, Shannon wiener index, Evenness index, and descriptive analysis. The result showed that the level of diversity of plant species in HCV in each company is different. The highest value of plant based species richness Margalef index is PTPN V (16,836), while the value of the highest plant species diversity by Shannon wiener index is PT MUP (3,773). The highest value by evenness index is PT MUP (0,901).Community interaction that occurs in the region of HCV is utilization such as animal feed, food plants, firewood, and the honey-producing trees.Keywords: diversity of species,interaction, oil palm plantations, plants